2021
DOI: 10.1177/00812463211015348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 on the economy and mental health of young people in South Africa: opportunities for strengthening social protection programmes by integrating mental health

Abstract: The majority of COVID-19 cases in sub-Saharan Africa are found in South Africa, where one third of young people are not in employment, education or training. As the world continues to fight the COVID-19 virus spread, an increasing volume of studies are analysing and trying to predict the consequences of the pandemic on the economy and on physical and mental health. This article describes the economic and psychological impact of COVID-19 in South Africa’s youth specifically, the efforts made to tackle these iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A recent study amongst workers in South Africa also found that social distancing had led to loneliness amongst adults [ 39 ]. Additionally, evidence suggests a link between experienced loneliness, “containment-related stress” related to stay-at-home lockdown restrictions, and mental health issues such as anxiety, depression and suicide ideation [ 2 , 40 ]. Death of parents or caregivers also adds additional stressors to adolescents’ mental health, and can lead to increased risk behaviours [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study amongst workers in South Africa also found that social distancing had led to loneliness amongst adults [ 39 ]. Additionally, evidence suggests a link between experienced loneliness, “containment-related stress” related to stay-at-home lockdown restrictions, and mental health issues such as anxiety, depression and suicide ideation [ 2 , 40 ]. Death of parents or caregivers also adds additional stressors to adolescents’ mental health, and can lead to increased risk behaviours [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to AGYW in our study, anxiety and uncertainty about the future, leading to a sense of hopelessness and despondence was also found amongst South African university students [ 46 ]. Feelings of defeat and hopelessness about educational and career prospects, accompanied by negative perceptions of self-potential, apathy and avoidance of opportunities, are not only distressing due to economic anxiety, but could link to psychological distress related to loss of purpose and agency, and are likely to make it more difficult for young people to escape circumstances of poverty and adversity [ 2 , 4 ]. To mitigate these impacts, efforts need to be made to create an enabling environment to foster hope amongst adolescents and young people in South Africa [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations